Burnout and emotional regulation: insights from students enrolled in higher education programs for initial teacher training - Ferreira, Júlia; Peixoto, Carla; Coelho, Vera; Barros, Sílvia; Sousa-Pereira, Fátima; Machado, Francisco; Marques-Pinto, Alexandra (Frontiers in Education, 2025)
Research has emphasized the importance of teachers developing their socioemotional competencies to effectively deal with the challenges associated with teaching, considering its impact on their occupational health and wellbeing, namely on the risk of experiencing burnout. However, there is a lack of studies on the relationship between these variables in initial teacher training courses for students. Therefore, explores students attending higher education programs for teaching certification burnout symptoms, examine differences in their burnout symptoms according to sociodemographic and academic factors, and analyze the predictive role of emotional regulation in the explanation of those symptoms. Data were collected using the Emotional Regulation Questionnaire and the Maslach Burnout Inventory—Students Survey. A total of 157 Portuguese students, attending bachelor's and master's degrees in initial teacher training courses, participated in the study. The results showed that students attending higher education courses for teacher training perceived low emotional exhaustion and cynicism and moderate academic efficacy. The criteria for burnout were met by 4.5% of participants, with high variability in burnout scores. Regression models explored how emotional regulation strategies were associated with burnout symptoms, controlling for socio-demographic and academic variables. Before conducting the regression models, we explored associations between both socio-demographic and academic variables and emotional regulation strategies, finding that study cycle and worker-student status were significantly associated with emotional exhaustion, with master's students reporting higher levels of exhaustion compared to bachelor's students, and worker-students reporting lower levels of exhaustion. Additionally, worker-students also exhibited lower levels of cynicism. Regarding academic efficacy, significant differences were found for gender, study cycle, and worker-student status, with females, master's students, and worker-students reporting higher levels of professional efficacy. The results suggest the importance of initial teacher training schools designing and implementing socioemotional learning programs that may promote effective emotional regulation competencies.